Efficacy of two adjuvants administrated with a novel hydrogen peroxide-inactivated vaccine against Streptococcus agalactiae in Nile tilapia fingerlings - Ramos-Espinoza, Fernando Carlos [UNESP]; Cueva-Quiroz, Victor Alexander [UNESP]; Yunis-Aguinaga, Jefferson [UNESP]; Alvarez-Rubio, Norquis Caled [UNESP]; Paganoti de Mello, Nicoli [UNESP]; Engrácia de Moraes, Julieta Rodini [UNESP] (Elsevier, 2020)
Streptococcus agalactiae is considered the main bacterial pathogen in cultured Nile tilapia. Formaldehyde-inactivated vaccines are the most accepted method for prevention and control of the disease. However, alternative inactivation methods for S. agalactiae vaccines have not been fully explored. Recently, we developed a hydrogen peroxide-inactivated vaccine against S. agalactiae with moderate efficacy, with the possibility to improve vaccine efficacy by adding adjuvants. The current study compared the efficacy of aluminum hydroxide and Freund's incomplete adjuvant (FIA) incorporated into a novel hydrogen peroxide-inactivated intraperitoneal vaccine against S. agalactiae for Nile tilapia fingerlings. The relative percentage survival (RPS) for aluminum hydroxide-adjuvanted vaccine (59.3%), and FIA-adjuvanted vaccine (77.8%) were higher than the vaccine without adjuvant (40.7%). In addition, fish immunized with aluminum hydroxide-adjuvanted vaccine had significantly higher levels of specific antibodies than control fish at 4 weeks post vaccination (wpv). Blood lymphocytes counts showed a decrease in vaccinated groups when compared to control fish, suggesting white cells migration to the tissues where antigen presentation is ongoing. Fish that received FIA-adjuvanted vaccine exhibited persistence of adjuvant deposits on intraperitoneal surfaces for at least 4 wpv that may be related to its superior performance compared to aluminum hydroxide adjuvanted vaccine, which did not evidence any type of deposit at any sampling times. The results observed in this study demonstrate that hydrogen peroxide-inactivated vaccine administered with either aluminum hydroxide or FIA induce optimal levels of protection, with a superior performance for FIA vaccine, which could be a good alternative to conventional formaldehyde-inactivated vaccines against S. agalactiae, due to its shorter manufacture time, and less toxicity.
Keywords: Aluminum hydroxide; Freund incomplete adjuvant; Immune response; Oreochromis niloticus; Vaccine efficacy